Enhancing the diagnosis of fabry disease in cardiology with a targeted information: a before–after control–impact study. Issue 1 (13th March 2017) - Savary, Anne-Louise; Morello, Remy; Brasse-Lagnel, Carole; Milliez, Paul; Bekri, Soumeya; Labombarda, Fabien
Abstract : Background: Cardiac complications in Fabry disease are frequent and dominated by a high frequency of left ventricular hypertrophy; therefore, cardiologists may have an essential role in screening for this disease. Providing cardiologists with targeted information on Fabry disease would be valuable and could reduce both diagnostic and therapeutic delays. The aim of this study was to evaluate the efficiency of such strategy for Fabry screening. Methods: We conducted a before–after control–impact study by comparing observations made before and after targeted information on Fabry disease among cardiologists. The information on Fabry disease consisted of (1) an educational booklet, (2) oral information and (3) screening kits. The programme was evaluated at the end of a 12-month study period. Results: Forty-two cardiologists participated to this study. None of them had conducted screening test and new diagnostic for Fabry disease in the 3 years prior the information. After the information, screening with dried blood spots was performed in 55 patients (ranged 18–77 years, men: 39) with cardiac monitoring for supposed sarcomeric hypertrophic cardiomyopathy (n=41) or unexplained left ventricular hypertrophy (n=14) from January 2015 to January 2016. Two new cases of Fabry disease were diagnosed (3.4%) in two men (ages 58 and 51 years). The information was deemed relevant in both content and structure and was deemed useful for everyday practice. Conclusion: Cardiologists valued the targeted information on Fabry disease. This information had a direct clinical impact by allowing the diagnosis of two new families with Fabry disease.